In-vitro Inhibition of Mineralisation of Urinary Stone Forming Minerals by Fruit Juices. - V. R.K. RAO, T.; BANO, SOFIA (Asian Journal of Chemistry, 2010)
Fruit juices, viz., juice of lemon varieties, orange, sweet orange, grape, pineapple, mango and amla have been studied as inhibitors in the mineralisation of urinary stone forming minerals, viz., calcium phosphate, oxalate or carbonate. Inhibition efficiency has been studied in different experimental models. Utility of these fruits, in urolithiasis inhibition has been discussed.